One Book One Teacher Program for Upgrading Teachers’ Writing Competence (A Descriptive Survey) - Hartono, Rudi; Purwanto, Bambang; Bahri, Seful (Language Circle: Journal of Language and Literature, 2019)
Writing competence is one of significant and basic demands for teachers in delivering their profession as educators. Many teachers feel that writing a book is a pride but it is too difficult for them to do. Many factors influence them not to start to write, such as inner motivation, institution supports, ideas, materials, and opportunities. For examples, many of them are lack of motivation to be confident course book writers, their institutions do not support their efforts and facilitate them well, they have no idea what they are going to write, they are not accustomed to provide their own lesson materials for their daily instructionÃ¢â‚¬â€only copying from books or other resources, and most of them do not have any opportunity at all to write a course book. Therefore to create teacher-writers and produce course books in one school, One Book One Teacher (OBOT) program comes as a solution. OBOT is a program designed for teachers to be a course book writer at schools. Recently we revealed that OBOT has potential activities as an integrated program in preparing teachers to be professional course book writers. In this study, to dig up their responses on course book writing activity and OBOT implementation in their school, we conducted a descriptive survey and observation on 13 teachers in Senior High School Bina Amal Semarang. We distributed questionnaires, tabulated, analyzed and interpreted the data, then drew the conclusion. The research results show that significantly OBOT encouraged teachers to write course book actively and led them to be productive course book writers.